Perancangan Produk Media Pembelajaran Untuk Anak Down Syndrome Studi Kasus Potads kota Surabaya - prayogi, sigit; kristianingrum, renaka; ngo, jenny (SNADES, 2024)
Helping these children learn and develop optimally by providing appropriate learning media is the main goal for overcoming learning media problems for children with Down syndrome (trisomy 21). Learning media that can help children with Down syndrome improve their reading, writing and arithmetic skills (academic skills). Learning media can also help children with Down syndrome develop the social skills, independence and self-confidence needed to interact with their surrounding environment. Apart from that, learning media can improve motor skills and coordination, improve language skills, improve problem-solving skills, and increase the interest and participation of Down syndrome children in their education. With the method of adapting learning media to the needs and abilities of each child, using visual media, using interactive media, and through multisensory learning experiences, such as learning through direct, visual and auditory experiences simultaneously. By overcoming learning media problems for children with Down syndrome trisomy 21 by increasing learning abilities, improving social skills, improving life skills, improving quality of life, and increasing self-confidence, we can help children with Down syndrome reach their maximum potential and become better members of society. independent and productive.